Charge-Mediated Co-assembly of Amphiphilic Peptide and Antibiotics Into Supramolecular Hydrogel With Antibacterial Activity - Xu, Lei; Shen, Qian; Huang, Linzhuo; Xu, Xiaoding; He, Huiyan (Frontiers in Bioengineering and Biotechnology, 2020)
Bacteria are the most common pathogens to induce surgical site infections, which usually cause significant postoperative morbidity and increased healthcare costs. Inhibition of bacteria adhesion and colonization is an effective strategy to prevent the spread of infection at the surgical sites. Hydrogels have recently emerged as promising antibacterial materials due to their unique three-dimensional structure, which could accommodate various antibacterial agents (e.g., antibiotics and cationic polymers with inherent antibacterial activity). Herein, arising from the abundant examples of protein self-assembly existing in nature, an amphiphilic peptide comprised of a hydrophobic naphthyl (Nap) acetyl tail and a hydrophilic peptide backbone was designed to construct supramolecular hydrogel for the sustained release of antibiotics polymyxin B. At a neutral pH, the negatively charged amphiphilic peptide could form electrostatic attraction interaction with the positively charged polymyxin B, which could thus drive the ionized peptide molecules to get close to each other and subsequently trigger the self-assembly of the amphiphilic peptide into supramolecular hydrogel via intermolecular hydrogen bonding interaction among the peptide backbones and π-stacking of the hydrophobic Nap tails. More importantly, the electrostatic attraction interaction between polymyxin B and the amphiphilic peptide could ensure the sustained release of polymyxin B from the supramolecular hydrogel, leading to an effective inhibition of Gram-negative bacteria Escherichia coli (E. coil) growth. Combining the good biocompatibility of the amphiphilic peptide, the supramolecular hydrogel developed in this work shows a great potential for the surgical site infection application.